Underage Widows and Widowers before the Law: Problem, Contestation and Legal Certainty in Marriage Dispensation - Muhammad Fauzinudin Faiz; Zezen Zainul Ali; Muhammad Taufiq (JURIS (Jurnal Ilmiah Syariah), 2023)
Increasing the minimum age for marriage has increased the community's efforts to obtain a marriage dispensation permit in court. Generally, this application is made by children who are not old enough and not yet married, but the facts on the ground state that there are widows and widowers under age who also apply for a marriage dispensation for the second time, this raises a new problem, namely legal uncertainty for the applicant. This study will explore the problems of an underage widow and widower in registering his second marriage and the contestation of authority in the marriage of underage widows and widowers. The study was conducted by looking at and analyzing several cases of application for dispensation for the marriage of underage widows and widowers in several Religious Courts (juridical normative) and mapping related documents (library research). Three important points are noted. First, when a widow and widower under the age of 19 applies for marriage registration at the Office of Religious Affairs but is refused and directed to apply for a dispensation to marry, while in the Religious Court, there are differences of opinion among judges in the application for dispensation to marry a second time, some reject, and some accept. Second, there is contestation between the Office of Religious Affairs and the Religious Courts in viewing dispensation for widow and widower marriage because of the different legal basis used. Third, despite the contestation between the two institutions, the Religious Courts, as justice-seeking agencies, must accept the application submitted to ensure legal certainty for its citizens, namely widows and widowers under age. Thus, this article recommends two actions: namely, the need for communication between the two executive and judicial institutions to discuss the issue of marriage dispensation for underage widows and widowers so as not to contradict each other and legal certainty for underage widows and widowers who want to marry is essential.